1989
DOI: 10.1002/star.19890410805
|View full text |Cite
|
Sign up to set email alerts
|

Material Characterization Studies of Maltodextrin Samples for the Use of Wall Material

Abstract: A few samples of maltodextrins procured commercially were studied in detail for some of their specific physicochemical qualities. In addition to the Dextrose Equivalent value (DE) the samples were analysed for their cold water solubility and clarity, percent age of cold water solubles, and total hydrolyzable carbohydrates. Samples were also analyzed for their hygroscopicity at different relative humidities varying from 40 to 95%. The carbohydrate profile was studied using HPLC and X‐ray diffraction pattern wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 2 publications
3
16
0
1
Order By: Relevance
“…2b, reduced amounts of maltodextrin caused the production of powders with a high amount of free oil; however, at high concentrations, this independent variable with high concentrations of Arabic gum had a positive effect on lowering the amount of free oil, indicating that the maltodextrin is one of the primary wall materials to protect the fish oil from environment and prevent its release outside of the capsules. The same results were obtained in a study by Raja et al (1989), in which the maltodextrins with a DE between 10 and 20 were demonstrated to have the greatest retention of core materials when combined with other wall materials. Studies conducted by Krishnan et al (2005), indicated that the combination of Arabic gum and maltodextrin was effective in the microencapsulation of cardamom oil; i.e., the retention of the core material was greater in blends of maltodextrin and Arabic gum.…”
Section: Centrifuge Stability Of the Emulsionsupporting
confidence: 80%
“…2b, reduced amounts of maltodextrin caused the production of powders with a high amount of free oil; however, at high concentrations, this independent variable with high concentrations of Arabic gum had a positive effect on lowering the amount of free oil, indicating that the maltodextrin is one of the primary wall materials to protect the fish oil from environment and prevent its release outside of the capsules. The same results were obtained in a study by Raja et al (1989), in which the maltodextrins with a DE between 10 and 20 were demonstrated to have the greatest retention of core materials when combined with other wall materials. Studies conducted by Krishnan et al (2005), indicated that the combination of Arabic gum and maltodextrin was effective in the microencapsulation of cardamom oil; i.e., the retention of the core material was greater in blends of maltodextrin and Arabic gum.…”
Section: Centrifuge Stability Of the Emulsionsupporting
confidence: 80%
“…However, the retention of emulsified ethyl butyrate during spray-drying was shown to be dependent on the maltodextrin concentration and the type of emulsifier . A maltodextrins characterization study published by Raja, Sankarikutty, Sreekumar, Jayalekshmy, & Narayanan (1989) showed that maltodextrins with dextrose equivalence between 10 and 20 fit in for using as wall material. Those maltodextrin samples show the highest retention of flavor because they could be dispersed in water up to 35.5% of the solution without haze formation.…”
Section: Carbohydratesmentioning
confidence: 98%
“…); a summary of these characteristics can be found in the noted references. [7,8] A few researchers have published moisture sorption isotherms or equilibrium moisture content data to be interpreted as such for gum acacia, [9,10] maltodextrin, [11][12][13][14] and OSAn-modified starch. [15] However, to our knowledge, there are no published moisture sorption isotherm data for carrier materials of controlled OSAn-modification.…”
Section: Introductionmentioning
confidence: 99%